Trade, Infrastructure and Development - Marcelo Olarreaga (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
We survey the literature on trade and development with a particular emphasis on the role of complementarities associated with trade infrastructure. The empirical literature shows that on average trade causes growth, but the relationship is far from being homogeneous across countries. Initial conditions matter. We focus on the role played by infrastructure. While the empirical literature shows that investment in soft and hard infrastructure have an unambiguously positive impact on trade flows, the theoretical literature argues that priority may be given to investments in domestic rather than international infrastructure in countries with relatively poor domestic infrastructure (Martin and Rogers, 1995). We found that the data supports this prediction.Keywords: Trade, Infrastructure, Development
Keywords: F10; O19; O47; 330